Selective Hydrogenation of Stearic Acid to 1-Octadecanol Using Bimetallic Palladium-Tin Supported on Carbon Catalysts at Mild Reaction Conditions - Rodiansono Rodiansono; Elisa Hayati; Atina Sabila Azzahra; Maria Dewi Astuti; Kamilia Mustikasari; Sadang Husain; Sutomo Sutomo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Bimetallic palladium-tin catalysts supported on microporous carbon (denoted as Pd-Sn(x)/C, loading amount of Pd = 5 wt% and x = Pd/Sn molar ratio; c.a. 3.0; 1.5; and 1.0) showed high selectivity in the hydrogenation of stearic acid towards 1-octadecanol (stearyl alcohol) under mild reaction conditions. Pd-Sn(x)/C catalysts were synthesized via the hydrothermal method at temperature of 150 °C for 24 h, and reduced with H2 at 400 °C for 3 h. Pd-Sn(1.5)/C catalyst exhibited the highest yield of stearyl alcohol (1-octadecanol) (up to 73.2%) at 100% conversion of stearic acid at temperature 240 °C, initial H2 pressure of 3.0 MPa, a reaction time of 13 h, and in 2-propanol/water solvent. The high selectivity of alcohols over Pd-Sn(1.5)/C catalyst can be attributed to the formation of bimetallic Pd-Sn alloy phases (e.g. Pd3Sn and Pd3Sn2) as obviously depicted by XRD analysis. The presence of co-promotor Sn and the formation of bimetallic may play a pivotal role in the high selectivity of 1-octadecanol. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).